Inflammatory responses in the Japanese pufferfish (Takifugu rubripes) head kidney cells stimulated with an inflammasome-inducing agent, nigericin - Bilen, Soner; Biswas, Gouranga; Otsuyama, Shohei; Kono, Tomoya; Sakai, Masahiro; Hikima, Jun-ichi (Elsevier BV, 2014)
A cytosolic receptor complex called inflammasome is responsible for mounting inflammatory response by releasing pro-inflammatory cytokines, interleukin (IL)-1β and IL-18. However, inflammatory cascades mediated by the inflammasome are unknown in a lower vertebrate like fish. Therefore, in an in vitro experiment, in order to obtain a preliminary information, we conducted transcriptomic analysis of 18 cytokines including pro-inflammatory cytokines in the Japanese pufferfish (Takifugu rubripes) head kidney (HK) cells stimulated with an inflammasome-inducing agent, nigericin, and a combination of nigericin and LPS by a multiplex RT-PCR assay (GenomeLab Genetic Analysis System, GeXPS; Beckman Coulter Inc.). Furthermore, expression of IL-1β, IL-6, IL-18, nuclear factor (NF)-κB, nucleotide-binding oligomerization domain 2 (NOD2) and NOD-like receptor X1 (NLRX1) genes was examined in HK cells by a quantitative real-time PCR. Additionally, to confirm functionality of activated inflammatory immunity, we also assessed phagocytic activity, superoxide anion production (NBT assay) and lysozyme activity in the nigericin-stimulated HK cells. An increased gene expression of pro-inflammatory cytokines (IL-1β and IL-18), NF-κB and NOD2 was recorded in nigericin and combined nigericin+LPS- stimulated HK cells. Enhanced cellular (phagocytic activity and NBT assay) and humoral (lysozyme activity) immune parameters in the stimulated cells confirmed induction of inflammatory response. Results suggested probable activation of inflammasome components for processing of the inflammatory cytokines in the Japanese pufferfish.
Keywords: Fish Proteins; Lipopolysaccharides; Immunity, Cellular; Inflammasomes; Nod2 Signaling Adaptor Protein; Transcription Factor RelA; Gene Expression; Head Kidney; Immunity, Humoral; Takifugu; Mitochondrial Proteins; Nigericin; Animals; Cytokines; Cells, Cultured; 2. Zero hunger; 3. Good health